Análise cinemática e cinética da articulação do joelho no exercício de agachamento com o uso de resistência variável e constante - Martins, Elisandro de Assis (2017)
Squatting is a functional and paramount exercise in everyday activities, and is fundamental in day-to-day actions such as sitting, crouching to pick up objects, going up and down stairs, transposing objects, among others. It is one of the exercises most commonly used in the processes of rehabilitation and physical training, however this is one of the exercises that most promotes joint loads and can contribute to the appearance of injuries and degeneration. The aim of this study was to compare the effects of the application of constant and variable resistance during the execution of the squatting exercise on the torques in the knee joint. Twenty-one subjects participated in the study, being healthy male practitioners of regular physical activity involving strength training. The tests occurred on two force platforms synchronized to a cinemetry system. The torque values presented significant differences in the sagittal and frontal planes and no differences in the transverse plane. In the sagittal and frontal planes were found smaller magnitudes of extensor and abductor torque, respectively, in the condition of variable resistance in the angles of greater knee flexion and also of flexor torque in the final phase of the sagittal plane movement, when compared to the constant resistance condition. In conclusion, the use of variable resistance compared to the constant resistance appears to be a considerable alternative when the objective is to minimize internal loads on the knee joint in squatting exercises.